2004
DOI: 10.1002/biof.552210109
|View full text |Cite
|
Sign up to set email alerts
|

Food‐derived peptides and intestinal functions

Abstract: Many researchers have reported that food proteins and their peptides expressed a variety of functions in the body, including a reduction of blood pressure, modulation of immune cell functions, and regulation of nerve functions. However, food-derived proteins and peptides also play important roles in the intestinal tract before being absorbed. For example, some of the proteins and peptides can regulate the activity of digestive enzymes in the intestinal tract, thereby modulating the nutrient absorption in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
9

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 18 publications
1
108
0
9
Order By: Relevance
“…This protein material is hydrolyzed by luminal gastric and pancreatic enzymes and epithelial brush border membrane peptidases into a complex mixture of oligopeptides, dipeptides, tripeptides, and free amino acids that transit and are progressively absorbed along the small intestine. Different studies have suggested that bioactive peptides released from dietary protein during digestion could exert metabolic and physiologic actions by acting on specific targets at the digestive level or after absorption (2)(3)(4)(5), and some studies have particularly identified potential bioactive peptides in the sequence of milk proteins (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein material is hydrolyzed by luminal gastric and pancreatic enzymes and epithelial brush border membrane peptidases into a complex mixture of oligopeptides, dipeptides, tripeptides, and free amino acids that transit and are progressively absorbed along the small intestine. Different studies have suggested that bioactive peptides released from dietary protein during digestion could exert metabolic and physiologic actions by acting on specific targets at the digestive level or after absorption (2)(3)(4)(5), and some studies have particularly identified potential bioactive peptides in the sequence of milk proteins (6).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, this study aimed to characterize digestion products and, particularly, peptides released in the jejunum after ingestion of either milk casein or whey proteins (WPs) 5 in healthy human subjects. We used a gastrointestinal tube technique to collect effluents as well as mass spectrometry (MS) to extensively identify and quantify milk protein-derived peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Tests encompassing hypertensive animals and human clinical trials have shown that certain sequences can lower blood pressure; however, it is difficult to establish a direct link between the ability to inhibit ACE in vitro and the actual antihypertensive activity in vivo. Knowledge of the mechanism of action of such bioactive peptides is obviously crucial before manufacture of functional foods with physiological properties is in order [268].…”
Section: Bioavailabilitymentioning
confidence: 99%
“…In addition, a group of peptides can also act as biocarriers for Ca and other minerals, increasing their bioavailability (8,9) . The activities of milk peptides and products containing them have been recently reviewed elsewhere (1,2) .…”
Section: Food Bioactive Peptidesmentioning
confidence: 99%